2013
DOI: 10.1016/j.ijcard.2012.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis in asplenia syndrome with congenital heart disease: A previously unrecognized risk factor for thromboembolism

Abstract: Persistent thrombocytosis is present in patients with asplenia syndrome. It may greatly contribute to the development of thromboembolism during the management of congenital heart disease than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Effective prenatal detection and diagnosis of splenic abnormalities are beneficial for uncovering more serious developmental defects. For example, splenomegaly is often accompanied by transplacental infection, immunological disorders, congestive heart failure, and congenital anemia . Previous research has shown that fetal spleen size can serve as a predictor of the prognosis of hemoglobin Bart's disease .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective prenatal detection and diagnosis of splenic abnormalities are beneficial for uncovering more serious developmental defects. For example, splenomegaly is often accompanied by transplacental infection, immunological disorders, congestive heart failure, and congenital anemia . Previous research has shown that fetal spleen size can serve as a predictor of the prognosis of hemoglobin Bart's disease .…”
Section: Introductionmentioning
confidence: 99%
“…For example, splenomegaly is often accompanied by transplacental infection, immunological disorders, congestive heart failure, and congenital anemia. 1,[3][4][5][6] Previous research has shown that fetal spleen size can serve as a predictor of the prognosis of hemoglobin Bart's disease. 7 Early ultrasonographic examination is 1.5 times more likely to detect complex developmental defects during fetal development rather than isolated malformations.…”
Section: Introductionmentioning
confidence: 99%
“…These clinical features have important functional implications. For instance, those with isomerism may have functional asplenia even in the setting of multiple spleens or a solitary, normally located spleen, leaving them prone to bacteremia from encapsulated organisms, thrombocytosis, and thromboembolic events . Those with left bronchial isomerism may be more likely to have recurrent sinopulmonary symptoms and may have a higher need for supplemental oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…8 Splenic dysfunction leads to increased risk of infections and thromboembolic events. 9,10 Abnormal neurologic function reflects the malformations involving the central nervous system, while cardiac physiology is self-evidently impacted by the variety of cardiac malformations. [11][12][13] The cardiac manifestations of heterotaxy themselves also go beyond the anatomic abnormalities, since the isomeric changes also involve the cardiac conduction system.…”
Section: Introductionmentioning
confidence: 99%